2015
DOI: 10.2135/cropsci2015.03.0183
|View full text |Cite
|
Sign up to set email alerts
|

Degenerate Oligonucleotide Primed–Polymerase Chain Reaction‐Based Chromosome Painting of P Genome Chromosomes in Agropyron cristatum and Wheat–A. cristatum Addition Lines

Abstract: Agropyron cristatum (L.) Gaertn. (2n = 4x = 28, PPPP), a wild relative of wheat, could provide many desirable genes for wheat improvement. Microdissection and degenerate oligonucleotide primed –polymerase chain reaction (DOP–PCR) is an effective way to isolate specific sequences. The development of specific sequences and functional markers of P genome could lay the foundation for gene mapping and cloning. In this study, chromosomes 6PS and 6PL were microdissected from wheat–A. cristatum 6PS and 6PL addition li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Molecular markers provide a rapid, reliable, easy, high-throughput method for detecting the alien chromosome segments. We previously showed that repeat sequence markers can detect A. cristatum alien chromosomes in a common wheat background 18 , 21 . However, repeat sequence markers are distributed throughout a whole chromosome and cannot distinguished specific chromosome fragment loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular markers provide a rapid, reliable, easy, high-throughput method for detecting the alien chromosome segments. We previously showed that repeat sequence markers can detect A. cristatum alien chromosomes in a common wheat background 18 , 21 . However, repeat sequence markers are distributed throughout a whole chromosome and cannot distinguished specific chromosome fragment loci.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al . (2015) used the degenerate oligonucleotide-primed (DOP)-PCR products of microdissected 6PS as a fluorescence in situ hybridization (FISH) probe to identify P genome chromatin in wheat- A. cristatum introgression lines, but the method relied on cytological techniques 21 .…”
Section: Introductionmentioning
confidence: 99%
“…GISH was performed in root tip cells to identify the 6P addition chromosomes as described by Han et al [ 73 ]. A. cristatum genomic DNA was used as a probe, and Fukuho genomic DNA was used as a blocker to detect A. cristatum chromosomes in the wheat background.…”
Section: Methodsmentioning
confidence: 99%
“…Two A. cristatum- specific probes (pAcTRT1 and pAcpCR2), which distribute on the telomeric and pericentromeric regions of A. cristatum chromosomes, were used as FISH probes. The probes were recovered from degenerate oligonucleotide primed-polymerase chain reaction (DOP-PCR) products of microdissected chromosome 6PS 11,12 . The two sequences were registered in NCBI GenBank with the accession numbers KP231286 and KX390711.…”
Section: Methodsmentioning
confidence: 99%